2016
DOI: 10.1111/imb.12271
|View full text |Cite
|
Sign up to set email alerts
|

Novel seminal fluid proteins in the seed beetle Callosobruchus maculatus identified by a proteomic and transcriptomic approach

Abstract: The seed beetle Callosobruchus maculatus is a significant agricultural pest and increasingly studied model of sexual conflict. Males possess genital spines that increase the transfer of seminal fluid proteins (SFPs) into the female body. As SFPs alter female behaviour and physiology, they are likely to modulate reproduction and sexual conflict in this species. Here, we identified SFPs using proteomics combined with a de novo transcriptome. A prior 2D-sodium dodecyl sulphate polyacrylamide gel electrophoresis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…Since there is no courtship behaviour in burying beetles, nor the presentation of any nuptial gifts, nor any pheromonal displays when beetles are in close proximity, we suggest these effects could be due to differences in ejaculate composition. Detailed analyses of Drosophila and Tribolium ejaculates, for example, have found that they contain a multitude of proteins which alter female physiology in diverse ways (Sirot et al 2011;Yamane et al 2015;Bayram et al 2017;Wigby et al 2016). Furthermore, smaller Drosophila allocate more proteins from their accessory gland to their ejaculate than do larger males (Wigby et al 2016) and a mechanism like this could account for the differences we found between Small and Large burying beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no courtship behaviour in burying beetles, nor the presentation of any nuptial gifts, nor any pheromonal displays when beetles are in close proximity, we suggest these effects could be due to differences in ejaculate composition. Detailed analyses of Drosophila and Tribolium ejaculates, for example, have found that they contain a multitude of proteins which alter female physiology in diverse ways (Sirot et al 2011;Yamane et al 2015;Bayram et al 2017;Wigby et al 2016). Furthermore, smaller Drosophila allocate more proteins from their accessory gland to their ejaculate than do larger males (Wigby et al 2016) and a mechanism like this could account for the differences we found between Small and Large burying beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the genital jaws of C. subinnotatus may also affect female uptake of male seminal fluid, although this may then be manifested as elevated female egg production in this species. We note that that male seminal fluid in seed beetles contains a very large number of proteins, some of which affect male fertilization success and others that affect female egg production (Goenaga et al, 2015; Yamane et al, 2015; Bayram et al, 2017). Needless to say, given everything else equal, male postmating reproductive success is elevated by an increase in female egg production (Arnqvist and Rowe, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Our results suggest that the genital jaws of C. subinnotatus may also affect female uptake of male seminal fluid, although this may then be manifested as elevated female egg production in this species. We note that that male seminal fluid in seed beetles contains a very large number of proteins, some of which affect male fertilization success and others that affect female egg production ( Goenaga et al, 2015 ; Yamane et al, 2015 ; Bayram et al, 2017 ). Needless to say, given everything else equal, male postmating reproductive success is elevated by an increase in female egg production ( Arnqvist and Rowe, 2005 ).…”
Section: Discussionmentioning
confidence: 96%